Synthesis and color mixing of semiconductor nanocrystals for optoelectronic application. - Ridwan Salim Sanad. (2011)
In this project, synthesis, computation and color mixing of 0-D semiconductor nanocrystals, also known as quantum dots, for solid state lighting was employed. It was motivated by the emergence of light emitting diode as future lighting candidate, which require versatile combination with nanocrystals to create high quality white light.